Exploring a supramolecular gel to in‐situ crystal fabrication from the low molecular weight gelators: a crystal engineering approach towards microelectronic device application. Issue 12 (21st March 2023) - Dhibar, Subhendu; Pal, Baishakhi; Karmakar, Kripasindhu; Kundu, Sandip; Bhattacharjee, Subham; Sahoo, Rupam; Mehebub Rahaman, SK.; Dey, Dhananjay; Pratim Ray, Partha; Saha, Bidyut
Abstract: A novel functional supramolecular gel (SA‐MEA) has been produced through the mixing of succinic acid and monoethanolamine directly in DMF medium under ambient conditions. The semi‐solid and viscoelastic nature of mechanically stable SA‐MEA gel has been established through the rheological analysis. The major chemical components of the gel are confirmed by EDX elemental mapping, while FESEM microstructural analysis investigates the morphological patterns of the gel. The gel gives rise to crystalline materials at room temperature and in the absence of external stimuli. Single‐crystal diffraction study of the in‐situ generated crystals shows the existence of different supramolecular synthons involving the hydrogen‐bonding interactions (N−H⋅⋅⋅O and O−H⋅⋅⋅O) leading to the formation of graph set motifs. These structural building blocks provide the stability to hold the overall molecular framework of SA‐MEA gel. Moreover, the contribution of O⋅⋅⋅H/H⋅⋅⋅O contacts plays a crucial role in this gel formation, which is established from the Hirshfeld surfaces along with linked 2D fingerprint patterns of the plot for both molecular components. Additionally, the SA‐MEA gel's supramolecular structure exhibits electrical conductivity, which was exploited to construct an electronic device with a metal‐semiconductor (MS) junction. Analyses of the gel's electrical properties were done in‐depth. Inclusive, this work demonstrates that the SA‐MEA gel may be used to create a semi‐conductive microelectronic device, such as a Schottky barrier diode. Abstract : Organic acid succinic acid and monoethanolamine used as low molecular weight gelators to synthesize a novel supramolecular gel to in‐situ generated crystals in presence of DMF solvent at room temperature, offers semiconducting application as a microelectronic device like the Schottky barrier diode at room temperature.